2017
DOI: 10.1186/s12889-016-3972-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in TB patients: a 10-year electronic record review in a South African province

Abstract: BackgroundSince 1990, reduction of tuberculosis (TB) mortality has been lower in South Africa than in other high-burden countries in Africa. This research investigated the influence of routinely captured demographic and clinical or programme variables on death in TB patients in the Free State Province.MethodsA retrospective review of case information captured in the Electronic TB register (ETR.net) over the years 2003 to 2012 was conducted. Extracted data were subjected to descriptive and logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
43
3
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 22 publications
17
43
3
4
Order By: Relevance
“…In this study, patients aged 40 years and above were at higher risk of death. This finding is consistent with those of prospective observational studies in Taiwan (Feng et al, 2011) and South Africa (Heunis et al, 2017). Being illiterate was also a risk factor for mortality among TB-HIV co-infected patients.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, patients aged 40 years and above were at higher risk of death. This finding is consistent with those of prospective observational studies in Taiwan (Feng et al, 2011) and South Africa (Heunis et al, 2017). Being illiterate was also a risk factor for mortality among TB-HIV co-infected patients.…”
Section: Discussionsupporting
confidence: 91%
“…TB is the most common opportunistic infection, and several studies have shown that it is the leading cause of death among people living with HIV/AIDS [45,46], accounting for approximately 25% of HIV/AIDS deaths. In this analysis, similar to other studies [13,39], a 62-fold higher risk of TB death was identified among seropositive patients who started TB treatment. The fact that there were 319 HIV positive individuals that died due to TB and not due to AIDS with TB as an associate cause in our cohort probably reflects misclassification of cause of death errors.…”
Section: [Insert Table 2 Here] Discussionsupporting
confidence: 88%
“…In this analysis, individuals aged 60 years or older had a higher chance of death in the different causes analyzed. Similar results have been described by other authors [34,39] The fact that TB in older individuals significantly increases the chances of death should be considered when following up these patients throughout their treatment. The coexistence of other diseases related to old age may be associated with late diagnosis of TB due to atypical clinical presentation of the symptoms or the development of extra-pulmonary forms hard to diagnose, which can complicate the clinical picture and increase the risk of evolution to death.…”
Section: [Insert Table 2 Here] Discussionsupporting
confidence: 87%
“…[1] Thirdly, increased integration of TB and HIV services at a primary care level together with political attention, civil society mobilisation around TB and HIV, and the launch of a national HIV/ TB campaign in 2011 have helped reduce deaths from TB. [16] However, there are still some groups of people who are at increased risk of TB-related mortality.…”
Section: Discussionmentioning
confidence: 99%